Bebas Nyeri Low Back Pain (LBP) dengan Terapi Infusa Air Daun Pala di Desa Boiyauw Kecamatan Kepulauan Banda - Yerry Soumokil; Fanny Sabban (Jurnal Masyarakat Mengabdi Nusantara, 2024)
One of the plants that can be used as a pain reliever is Nutmeg Leaves. One of the compounds contained in nutmeg leaves is phenolic compounds. These phenolic compounds play a role in the treatment and prevention of diseases including as antioxidants and are able to overcome health problems such as lower back pain. Purposes : to provide information about the benefits of boiled water from nutmeg leaves to overcome Low Back Pain (LBP) or lower back pain in the community in Boiyauw Village, Banda, Maluku. Method: by providing information through health education. The media used are leaflets, power point presentations, samples of boiled water from nutmeg leaves. Results: It is expected that there will be changes in participant behavior when positioning themselves at work and that they can utilize nutmeg leaves as a family medicinal plant to reduce or relieve lower back pain.